Pengaruh Disiplin Kerja dan Lingkungan Kerja terhadap Kinerja Karyawan di CV. Putra Pelopor Pionir (Bohopanna) Semarang - Aminah Aminah; Wulandari Wulandari (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
Human resources are a strategic asset that significantly determines a company's operational effectiveness and efficiency. This study is motivated by the importance of human resource management, particularly in the aspects of work discipline and work environment, as key factors influencing employee performance. The research was conducted at CV. Putra Pelopor Pionir (Bohopanna) Semarang, a fast-growing local brand in baby and children's fashion that has expanded into international markets. Internal issues such as high absenteeism, tardiness, and inconsistent adherence to work instructions highlight the need for a thorough evaluation of the existing work conditions. This study aims to determine the extent to which work discipline and the work environment affect employee performance at Bohopanna Semarang. Using a quantitative approach and data analysis of 100 employees, the findings reveal that work discipline has a significant influence on employee performance. High levels of discipline, indicated by punctuality and compliance with rules, contribute to a stronger work ethic. In addition, the work environment also significantly affects performance, where supportive physical and social conditions enhance employee motivation and productivity. The study concludes that both independent variables—work discipline and work environment—positively and significantly contribute to employee performance, both partially and simultaneously. These findings offer practical recommendations for company management to strengthen discipline policies and improve the work environment to support organizational goals.